European arrest warrants : an inspection of the Serious Organised Crime Agency's data, systems and processes for dealing with European arrest warrants /: an inspection of the Serious Organised Crime Agency's data, systems and processes for dealing with European arrest warrants. (June 2013) - Great Britain., Her Majesty's Inspectorate of Constabulary,
No abstract available